Comparative analysis of ChatGPT and Grammarly in supporting grammar correction and writing development in EFL students - Prasetya, Rizky; Syarif, Achmad; Mayof, Adnan (English Education Department, Universitas Islam Indonesia, 2026)
This study investigates the effectiveness of ChatGPT and Grammarly as AI-powered tools for providing corrective feedback and supporting academic writing development among English as a Foreign Language (EFL) university students. A mixed-methods quasi-experimental design was employed, involving 300 participants divided into two experimental groups: one using ChatGPT and the other using Grammarly, over a four-week intervention period. Data were collected through perception questionnaires, writing tasks, grammar correction accuracy analysis, and student reflection journals. Descriptive statistics and paired samples t-tests indicated that students perceived ChatGPT to be more effective in improving grammar, increasing confidence, and enhancing understanding of grammar rules. Simultaneously, both tools were similarly rated in terms of clarity of feedback. The Wilcoxon Signed-Rank Test revealed that ChatGPT significantly outperformed Grammarly in terms of correction accuracy across most grammar categories. A Chi-square test of independence confirmed a statistically significant association between tool use and correction performance according to error type. Thematic analysis of student reflections identified five key themes: awareness of grammar rules, writing confidence, vocabulary and style, motivation to improve, and learning autonomy. ChatGPT was more closely associated with deeper learning and critical engagement, whereas Grammarly was valued for quick, surface-level corrections. Overall, the findings suggest that while both tools contribute to EFL writing development, ChatGPT offers greater pedagogical value through its interactive and explanatory feedback, making it a more effective tool for fostering writing improvement and learner autonomy in academic contexts.